Managers' experiences of prevention and management of workplace violence against health care staff: A descriptive exploratory study. (10th April 2019) - Morphet, Julia; Griffiths, Debra; Beattie, Jill; Innes, Kelli
Abstract: Aim: To examine health care managers' and health and safety staff experiences of prevention and management of workplace violence against staff. Background: Employers have a responsibility to protect employees from workplace violence. The varied care settings present challenges for those responsible for ensuring safety. Method: Descriptive exploratory study using semi‐structured interviews with 99 participants responsible for workplace safety, from 29 health services across metropolitan and regional Victoria, Australia. Interviews were audio‐recorded, transcribed and thematically analysed. Results: Five themes were identified: Workplace violence was accepted as "part of the job"; Participants relied on government resources and networking to guide them; Working alone and home visiting was a risk factor; Participants demanded a single, state‐wide training programme; Sharing information is vital. Conclusions: Participants were acutely aware of the risks of violence towards staff, and of their responsibility in managing risks. Knowledge sharing and consistent, regular education can reduce the risks. Additional resources were required, particularly during home visits, or when working alone. Implications for Nursing Management: Managers need to prioritize resources such as reliable rapid response systems to prevent and manage violence, particularly against staff working alone or home visiting. Information sharing between health services and other agencies is important to reducing risk.